Drought and Warming‐Induced Drying Suppress Soil Respiration but Amplify Rewetting‐Induced Pulses in a Temperate Pasture - Pankaj Tiwari; Elise Pendall; Nicholas Wright‐Osment; Nor Azizah Kusai; Manjunatha H. Chandregowda; Awais Shakoor; Debjani Sihi; Sally A. Power; Eric A. Davidson; Catriona A. Macdonald (Global Change Biology, 2026)
As climate extremes intensify, interactions among environmental drivers are expected to alter soil respiration (SR) and its response to rewetting, increasing uncertainty in carbon‐climate feedbacks. However, the interactive effects of drought and warming, two commonly studied climate stressors, on SR remain elusive due to limited research and a lack of high‐resolution data. This study investigated overall SR (SR overall , encompassing both drying and rewetting phases) and rewetting‐induced respiration pulses (SR pulse ), along with their apparent sensitivity to temperature and moisture under factorial combinations of rainfall and warming treatments in a field‐based climate‐manipulation experiment conducted in a temperate pasture system in southeastern Australia. Rainfall extremes were derived from 30 years of regional climate records, while warming was imposed as a continuous, year‐round increase of +3°C. An automated flux monitoring system was deployed to measure hourly SR across eight campaigns from October 2023 to November 2024. The drivers of SR overall and SR pulse were identified by analyzing climatic variables together with soil parameters from rhizosphere and non‐rhizosphere zones. Drought and warming consistently suppressed SR overall but amplified SR pulse and moisture sensitivity. The interactive effects of both treatments on SR overall varied seasonally, shifting from additive in spring to antagonistic in summer and autumn, and synergistic in winter. Drought suppressed apparent temperature sensitivity (Q 10 ), but warming effects on Q 10 varied with moisture conditions. Soil temperature, moisture, and extractable C:N ratio from across rhizosphere and non‐rhizosphere soil were consistent predictors of SR overall and SR pulse but exerted opposing effects on the two components. These findings advance our understanding of how drought‐warming interactions shape both overall and pulse‐driven SR, providing a process‐based foundation for improving predictions of carbon‐climate feedbacks under intensifying climate extremes.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Microbial mechanisms of interactive climate-driven changes in soil N2O and CH4 fluxes: A global meta-analysis - Awais Shakoor; Elise Pendall; Catriona A. Macdonald (Journal of Environmental Management, 2025)

What Regulates Net Carbon Uptake in Coastal Ecosystems? - Elise Pendall (Global Change Biology, 2025)

The effects of climate warming and exogenous nitrogen input on soil N2O emissions from mangroves - Weimin Song; Yan Zhao; Jian Zhou; Jianxiang Feng; Zhonglei Wang; Guangxuan Han; Elise Pendall; Guanghui Lin (Soil Biology and Biochemistry, 2024)

Iron-bound organic carbon declined after estuarine wetland reclamation into paddy fields - Xuyang Liu; Weiqi Wang; Elise Pendall; Yunying Fang (Science of The Total Environment, 2024)

Does no-till crop management mitigate gaseous emissions and reduce yield disparities: An empirical US-China evaluation - Awais Shakoor; Elise Pendall; Muhammad Saleem Arif; Taimoor Hassan Farooq; Shahid Iqbal; Sher Muhammad Shahzad (Science of The Total Environment, 2024)

Healthy soil for healthy humans and a healthy planet - Peter M. Kopittke; Budiman Minasny; Elise Pendall; Cornelia Rumpel; Brigid A. McKenna (Critical Reviews in Environmental Science and Technology, 2024)

Microbial control of soil organic matter dynamics: Effects of land use and climate change - Suvendu Das; Elise Pendall; Ashish A. Malik; Paolo Nannipieri; Pil Joo Kim (Biology and Fertility of Soils, 2024)

Nitrification and urease inhibitors mitigate global warming potential and ammonia volatilization from urea in rice-wheat system in India: A field to lab experiment - Ranabir Chakraborty; Tapan Jyoti Purakayastha; Elise Pendall; Saptaparnee Dey; Niveta Jain; Sarvendra Kumar (Science of The Total Environment, 2023)

Green-up and brown-down: Modelling grassland foliage phenology responses to soil moisture availability - Jinyan Yang; Belinda E. Medlyn; Craig V.M. Barton; Amber C. Churchill; Martin G. De Kauwe; Mingkai Jiang; Arjunan Krishnananthaselvan; David T. Tissue; Elise Pendall; Sally A. Power (Agricultural and Forest Meteorology, 2023)

Ecological stoichiometry and fungal community turnover reveal variation among mycorrhizal partners in their responses to warming and drought - Haiyang Zhang; Amber C. Churchill; Ian C. Anderson; Chioma Igwenagu; Sally A. Power; Jonathan M. Plett; Catriona A. Macdonald; Elise Pendall; Yolima Carrillo; Jeff R. Powell (Molecular Ecology, 2023)
Symbiotic fungi mediate important energy and nutrient transfers in terrestrial ecosystems. Environmental change can lead to shifts in communities of symbiotic fungi, but the consequences of these shifts for nutrient dynamics among symbiotic partners are poorly understood. Here, we assessed variation in carbon (C), nitrogen (N) and phosphorus (P) in tissues of arbuscular mycorrhizal (AM) fungi and a host plant ( Medicago sativa ) in response to experimental warming and drought. We linked compositional shifts in AM fungal communities in roots and soil to variation in hyphal chemistry by using high‐throughput DNA sequencing and joint species distribution modelling. Compared to plants, AM hyphae was 43% lower in (C) and 24% lower in (N) but more than nine times higher in (P), with significantly lower C:N, C:P and N:P ratios. Warming and drought resulted in increases in (P) and reduced C:P and N:P ratios in all tissues, indicating fungal P accumulation was exacerbated by climate‐associated stress. Warming and drought modified the composition of AM fungal communities, and many of the AM fungal genera that were linked to shifts in mycelial chemistry were also negatively impacted by climate variation. Our study offers a unified framework to link climate change, fungal community composition, and community‐level functional traits. Thus, our study provides insight into how environmental change can alter ecosystem functions via the promotion or reduction of fungal taxa with different stoichiometric characteristics and responses.

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Soil disturbance and invasion magnify CO 2 effects on grassland productivity, reducing diversity - Dana M. Blumenthal; Yolima Carrillo; Julie A. Kray; Matthew C. Parsons; Jack A. Morgan; Elise Pendall (Global Change Biology, 2022)
Climate change, disturbance, and plant invasion threaten grassland ecosystems, but their combined and interactive effects are poorly understood. Here, we examine how the combination of disturbance and plant invasion influences the sensitivity of mixed‐grass prairie to elevated carbon dioxide (eCO 2 ) and warming. We established subplots of intact prairie and disturbed/invaded prairie within a free‐air CO 2 enrichment (to 600 ppmv) by infrared warming (+1.5°C day, 3°C night) experiment and followed plant and soil responses for 5 years. Elevated CO 2 initially led to moderate increases in biomass and plant diversity in both intact and disturbed/invaded prairie, but these effects shifted due to strong eCO 2 responses of the invasive forb Centaurea diffusa. In the final 3 years, biomass responses to eCO 2 in disturbed/invaded prairie were 10 times as large as those in intact prairie (+186% vs. +18%), resulting in reduced rather than increased plant diversity (−17% vs. +10%). At the same time, warming interacted with disturbance/invasion and year, reducing the rate of topsoil carbon recovery following disturbance. The strength of these interactions demonstrates the need to incorporate disturbance into predictions of climate change effects. In contrast to expectations from studies in intact ecosystems, eCO 2 may threaten plant diversity in ecosystems subject to soil disturbance and invasion.

Trading water for carbon in the future: Effects of elevated CO 2 and warming on leaf hydraulic traits in a semiarid grassland - Kevin E. Mueller; Troy W. Ocheltree; Julie A. Kray; Julie A. Bushey; Dana M. Blumenthal; David G. Williams; Elise Pendall (Global Change Biology, 2022)
The effects of climate change on plants and ecosystems are mediated by plant hydraulic traits, including interspecific and intraspecific variability of trait phenotypes. Yet, integrative and realistic studies of hydraulic traits and climate change are rare. In a semiarid grassland, we assessed the response of several plant hydraulic traits to elevated CO 2 (+200 ppm) and warming (+1.5 to 3°C; day to night). For leaves of five dominant species (three graminoids and two forbs), and in replicated plots exposed to 7 years of elevated CO 2 , warming, or ambient climate, we measured: stomatal density and size, xylem vessel size, turgor loss point, and water potential (pre‐dawn). Interspecific differences in hydraulic traits were larger than intraspecific shifts induced by elevated CO 2 and/or warming. Effects of elevated CO 2 were greater than effects of warming, and interactions between treatments were weak or not detected. The forbs showed little phenotypic plasticity. The graminoids had leaf water potentials and turgor loss points that were 10% to 50% less negative under elevated CO 2 ; thus, climate change might cause these species to adjust their drought resistance strategy away from tolerance and toward avoidance. The C4 grass also reduced allocation of leaf area to stomata under elevated CO 2 , which helps explain observations of higher soil moisture. The shifts in hydraulic traits under elevated CO 2 were not, however, simply due to higher soil moisture. Integration of our results with others' indicates that common species in this grassland are more likely to adjust stomatal aperture in response to near‐term climate change, rather than anatomical traits; this contrasts with apparent effects of changing CO 2 on plant anatomy over evolutionary time. Future studies should assess how plant responses to drought may be constrained by the apparent shift from tolerance (via low turgor loss point) to avoidance (via stomatal regulation and/or access to deeper soil moisture).

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Recovery from Severe Mistletoe Infection After Heat- and Drought-Induced Mistletoe Death - Anne Griebel; Daniel Metzen; Elise Pendall; Rachael H. Nolan; Hamish Clarke; Alexandre A. Renchon; Matthias M. Boer (Ecosystems, 2022)

Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems - Alison C. Bennett; Stefan K. Arndt; Lauren T. Bennett; Jürgen Knauer; Jason Beringer; Anne Griebel; Nina Hinko‐Najera; Michael J. Liddell; Daniel Metzen; Elise Pendall; Richard P. Silberstein; Timothy J. Wardlaw; et al. (Global Change Biology, 2021)
Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP ( T opt ). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecoregions across Australia ranging from tropical in the north to Mediterranean and temperate in the south. We applied a novel boundary‐line analysis to eddy covariance flux observations to (a) derive ecosystem GPP–Ta relationships and T opt (including seasonal analyses for five tropical savannas); (b) quantitatively and qualitatively assess GPP–Ta relationships within and among ecoregions; (c) examine the relationship between T opt and mean daytime air temperature (MDTa) across all ecosystems; and (d) examine how down‐welling short‐wave radiation (Fsd) and vapour pressure deficit (VPD) influence the GPP–Ta relationship. GPP–Ta relationships were convex parabolas with narrow curves in tropical forests, tropical savannas (wet season), and temperate forests, and wider curves in temperate woodlands, Mediterranean woodlands, and tropical savannas (dry season). Ecosystem T opt ranged from 15℃ (temperate forest) to 32℃ (tropical savanna—wet and dry seasons). The shape of GPP–Ta curves was largely determined by daytime Ta range, MDTa, and maximum GPP with the upslope influenced by Fsd and the downslope influenced by VPD. Across all ecosystems, there was a strong positive linear relationship between T opt and MDTa (Adjusted R 2 : 0.81; Slope: 1.08) with T opt exceeding MDTa by >1℃ at all but two sites. We conclude that ecosystem GPP has adjusted to local MDTa within Australian broadleaf evergreen forests and that GPP is buffered against small Ta increases in the majority of these ecosystems.

Seasonal effects of altered precipitation regimes on ecosystem-level CO2 fluxes and their drivers in a grassland from Eastern Australia - Valentina Arca; Sally A. Power; Manuel Delgado-Baquerizo; Elise Pendall; Raúl Ochoa-Hueso (Plant and Soil, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Biogeographic variation in temperature sensitivity of decomposition in forest soils - Jinquan Li; Ming Nie; Elise Pendall; Peter B. Reich; Junmin Pei; Nam Jin Noh; Ting Zhu; Bo Li; Changming Fang (Global Change Biology, 2020)
Determining soil carbon (C) responses to rising temperature is critical for projections of the feedbacks between terrestrial ecosystems, C cycle, and climate change. However, the direction and magnitude of this feedback remain highly uncertain due largely to our limited understanding of the spatial heterogeneity of soil C decomposition and its temperature sensitivity. Here we quantified C decomposition and its response to temperature change with an incubation study of soils from 203 sites across tropical to boreal forests in China spanning a wide range of latitudes (18°16′ to 51°37′N) and longitudes (81°01′ to 129°28′E). Mean annual temperature (MAT) and mean annual precipitation primarily explained the biogeographic variation in the decomposition rate and temperature sensitivity of soils: soil C decomposition rate decreased from warm and wet forests to cold and dry forests, while Q 10‐MAT (standardized to the MAT of each site) values displayed the opposite pattern. In contrast, biological factors (i.e. plant productivity and soil bacterial diversity) and soil factors (e.g. clay, pH, and C availability of microbial biomass C and dissolved organic C) played relatively small roles in the biogeographic patterns. Moreover, no significant relationship was found between Q 10‐MAT and soil C quality, challenging the current C quality–temperature hypothesis. Using a single, fixed Q 10‐MAT value (the mean across all forests), as is usually done in model predictions, would bias the estimated soil CO 2 emissions at a temperature increase of 3.0°C. This would lead to overestimation of emissions in warm biomes, underestimation in cold biomes, and likely significant overestimation of overall C release from soil to the atmosphere. Our results highlight that climate‐related biogeographic variation in soil C responses to temperature needs to be included in next‐generation C cycle models to improve predictions of C‐climate feedbacks.

Warming and Elevated CO2 Interact to Alter Seasonality and Reduce Variability of Soil Water in a Semiarid Grassland - Dana M. Blumenthal; Kevin E. Mueller; Julie A. Kray; Daniel R. LeCain; Elise Pendall; Sara Duke; T. Jane Zelikova; Feike A. Dijkstra; David G. Williams; Jack A. Morgan (Ecosystems, 2018)

Elevated CO 2 and warming cause interactive effects on soil carbon and shifts in carbon use by bacteria - Yolima Carrillo; Feike Dijkstra; Dan LeCain; Dana Blumenthal; Elise Pendall (Ecology Letters, 2018)
Accurate predictions of soil C feedbacks to climate change depend on an improved understanding of responses of soil C pools and C use by soil microbial groups. We assessed soil and microbial C in a 7‐year manipulation of CO 2 and warming in a semi‐arid grassland. Continuous field isotopic labelling under elevated CO 2 further allowed us to study the dynamics of the existing C (Old C) in soil and microbes as affected by warming. Warming reduced soil C under elevated CO 2 but had no impact under ambient CO 2 . Loss of soil C under warming and elevated CO 2 was attributed to increased proportional loss of Old C. Warming also reduced the proportion of Old C in microbes, specifically the bacteria, but not the fungi. These findings highlight that warming impacts are C pool and microbial taxa dependent and demonstrate interactive effects of warming and atmospheric CO 2 on soil C.

Elevated CO 2 and water addition enhance nitrogen turnover in grassland plants with implications for temporal stability - Feike A. Dijkstra; Yolima Carrillo; Dana M. Blumenthal; Kevin E. Mueller; Dan R. LeCain; Jack A. Morgan; Tamara J. Zelikova; David G. Williams; Ronald F. Follett; Elise Pendall (Ecology Letters, 2018)
Temporal variation in soil nitrogen (N) availability affects growth of grassland communities that differ in their use and reuse of N. In a 7‐year‐long climate change experiment in a semi‐arid grassland, the temporal stability of plant biomass production varied with plant N turnover (reliance on externally acquired N relative to internally recycled N). Species with high N turnover were less stable in time compared to species with low N turnover. In contrast, N turnover at the community level was positively associated with asynchrony in biomass production, which in turn increased community temporal stability. Elevated CO 2 and summer irrigation, but not warming, enhanced community N turnover and stability, possibly because treatments promoted greater abundance of species with high N turnover. Our study highlights the importance of plant N turnover for determining the temporal stability of individual species and plant communities affected by climate change.

Bark beetle-induced tree mortality alters stand energy budgets due to water budget changes - David E Reed; Brent E Ewers; Elise Pendall; John Frank; Robert Kelly (Theoretical and Applied Climatology, 2018)

Faster turnover of new soil carbon inputs under increased atmospheric CO 2 - Kees Jan van Groenigen; Craig W. Osenberg; César Terrer; Yolima Carrillo; Feike A. Dijkstra; James Heath; Ming Nie; Elise Pendall; Richard P. Phillips; Bruce A. Hungate (Global Change Biology, 2017)
Rising levels of atmospheric CO 2 frequently stimulate plant inputs to soil, but the consequences of these changes for soil carbon (C) dynamics are poorly understood. Plant‐derived inputs can accumulate in the soil and become part of the soil C pool (“new soil C”), or accelerate losses of pre‐existing (“old”) soil C. The dynamics of the new and old pools will likely differ and alter the long‐term fate of soil C, but these separate pools, which can be distinguished through isotopic labeling, have not been considered in past syntheses. Using meta‐analysis, we found that while elevated CO 2 (ranging from 550 to 800 parts per million by volume) stimulates the accumulation of new soil C in the short term ( CO 2 does not affect the decomposition or the size of the old soil C pool over either temporal scale. Our results are inconsistent with predictions of conventional soil C models and suggest that elevated CO 2 might increase turnover rates of new soil C. Because increased turnover rates of new soil C limit the potential for additional soil C sequestration, the capacity of land ecosystems to slow the rise in atmospheric CO 2 concentrations may be smaller than previously assumed.

Challenging terrestrial biosphere models with data from the long‐term multifactor Prairie Heating and CO 2 Enrichment experiment - Martin G. De Kauwe; Belinda E. Medlyn; Anthony P. Walker; Sönke Zaehle; Shinichi Asao; Bertrand Guenet; Anna B. Harper; Thomas Hickler; Atul K. Jain; Yiqi Luo; Xingjie Lu; Kristina Luus; et al. (Global Change Biology, 2017)
Multifactor experiments are often advocated as important for advancing terrestrial biosphere models ( TBM s), yet to date, such models have only been tested against single‐factor experiments. We applied 10 TBM s to the multifactor Prairie Heating and CO 2 Enrichment ( PHACE ) experiment in Wyoming, USA . Our goals were to investigate how multifactor experiments can be used to constrain models and to identify a road map for model improvement. We found models performed poorly in ambient conditions; there was a wide spread in simulated above‐ground net primary productivity (range: 31–390 g C m −2 yr −1 ). Comparison with data highlighted model failures particularly with respect to carbon allocation, phenology, and the impact of water stress on phenology. Performance against the observations from single‐factors treatments was also relatively poor. In addition, similar responses were predicted for different reasons across models: there were large differences among models in sensitivity to water stress and, among the N cycle models, N availability during the experiment. Models were also unable to capture observed treatment effects on phenology: they overestimated the effect of warming on leaf onset and did not allow CO 2 ‐induced water savings to extend the growing season length. Observed interactive ( CO 2 × warming) treatment effects were subtle and contingent on water stress, phenology, and species composition. As the models did not correctly represent these processes under ambient and single‐factor conditions, little extra information was gained by comparing model predictions against interactive responses. We outline a series of key areas in which this and future experiments could be used to improve model predictions of grassland responses to global change.

Gross primary production responses to warming, elevated CO 2 , and irrigation: quantifying the drivers of ecosystem physiology in a semiarid grassland - Edmund M. Ryan; Kiona Ogle; Drew Peltier; Anthony P. Walker; Martin G. De Kauwe; Belinda E. Medlyn; David G. Williams; William Parton; Shinichi Asao; Bertrand Guenet; Anna B. Harper; Xingjie Lu; et al. (Global Change Biology, 2017)
Determining whether the terrestrial biosphere will be a source or sink of carbon (C) under a future climate of elevated CO 2 ( eCO 2 ) and warming requires accurate quantification of gross primary production ( GPP ), the largest flux of C in the global C cycle. We evaluated 6 years (2007–2012) of flux‐derived GPP data from the Prairie Heating and CO 2 Enrichment ( PHACE ) experiment, situated in a grassland in Wyoming, USA . The GPP data were used to calibrate a light response model whose basic formulation has been successfully used in a variety of ecosystems. The model was extended by modeling maximum photosynthetic rate ( A max ) and light‐use efficiency ( Q ) as functions of soil water, air temperature, vapor pressure deficit, vegetation greenness, and nitrogen at current and antecedent (past) timescales. The model fits the observed GPP well ( R 2 = 0.79), which was confirmed by other model performance checks that compared different variants of the model (e.g. with and without antecedent effects). Stimulation of cumulative 6‐year GPP by warming (29%, P = 0.02) and eCO 2 (26%, P = 0.07) was primarily driven by enhanced C uptake during spring (129%, P = 0.001) and fall (124%, P = 0.001), respectively, which was consistent across years. Antecedent air temperature (Tair ant ) and vapor pressure deficit ( VPD ant ) effects on A max (over the past 3–4 days and 1–3 days, respectively) were the most significant predictors of temporal variability in GPP among most treatments. The importance of VPD ant suggests that atmospheric drought is important for predicting GPP under current and future climate; we highlight the need for experimental studies to identify the mechanisms underlying such antecedent effects. Finally, posterior estimates of cumulative GPP under control and eCO 2 treatments were tested as a benchmark against 12 terrestrial biosphere models ( TBM s). The narrow uncertainties of these data‐driven GPP estimates suggest that they could be useful semi‐independent data streams for validating TBMs.

Cheatgrass is favored by warming but not CO 2 enrichment in a semi‐arid grassland - Dana M. Blumenthal; Julie A. Kray; William Ortmans; Lewis H. Ziska; Elise Pendall (Global Change Biology, 2016)
Elevated CO 2 and warming may alter terrestrial ecosystems by promoting invasive plants with strong community and ecosystem impacts. Invasive plant responses to elevated CO 2 and warming are difficult to predict, however, because of the many mechanisms involved, including modification of phenology, physiology, and cycling of nitrogen and water. Understanding the relative and interactive importance of these processes requires multifactor experiments under realistic field conditions. Here, we test how free‐air CO 2 enrichment (to 600 ppmv) and infrared warming (+1.5 °C day/3 °C night) influence a functionally and phenologically distinct invasive plant in semi‐arid mixed‐grass prairie. Bromus tectorum (cheatgrass), a fast‐growing Eurasian winter annual grass, increases fire frequency and reduces biological diversity across millions of hectares in western North America. Across 2 years, we found that warming more than tripled B. tectorum biomass and seed production, due to a combination of increased recruitment and increased growth. These results were observed with and without competition from native species, under wet and dry conditions (corresponding with tenfold differences in B. tectorum biomass), and despite the fact that warming reduced soil water. In contrast, elevated CO 2 had little effect on B. tectorum invasion or soil water, while reducing soil and plant nitrogen (N). We conclude that (1) warming may expand B. tectorum's phenological niche, allowing it to more successfully colonize the extensive, invasion‐resistant northern mixed‐grass prairie, and (2) in ecosystems where elevated CO 2 decreases N availability, CO 2 may have limited effects on B. tectorum and other nitrophilic invasive species.

Elevated carbon dioxide accelerates the spatial turnover of soil microbial communities - Ye Deng; Zhili He; Jinbo Xiong; Hao Yu; Meiying Xu; Sarah E. Hobbie; Peter B. Reich; Christopher W. Schadt; Angela Kent; Elise Pendall; Matthew Wallenstein; Jizhong Zhou (Global Change Biology, 2016)
Although elevated CO 2 ( eCO 2 ) significantly affects the α ‐diversity, composition, function, interaction and dynamics of soil microbial communities at the local scale, little is known about eCO 2 impacts on the geographic distribution of micro‐organisms regionally or globally. Here, we examined the β ‐diversity of 110 soil microbial communities across six free air CO 2 enrichment ( FACE ) experimental sites using a high‐throughput functional gene array. The β ‐diversity of soil microbial communities was significantly ( P CO 2 conditions, but declined significantly ( P eCO 2 with a slope of −0.0250 than at ambient CO 2 ( aCO 2 ) with a slope of −0.0231 although it varied within each individual site, indicating that the spatial turnover rate of soil microbial communities was accelerated under eCO 2 at a larger geographic scale (e.g. regionally). Both distance and soil properties significantly ( P β ‐diversity. This study provides new hypotheses for further understanding their assembly mechanisms that may be especially important as global CO 2 continues to increase.

Soil Microbes Compete Strongly with Plants for Soil Inorganic and Amino Acid Nitrogen in a Semiarid Grassland Exposed to Elevated CO2 and Warming - Janet Chen; Yolima Carrillo; Elise Pendall; Feike A. Dijkstra; R. Dave Evans; Jack A. Morgan; David G. Williams (Ecosystems, 2015)

Antecedent moisture and temperature conditions modulate the response of ecosystem respiration to elevated CO 2 and warming - Edmund M. Ryan; Kiona Ogle; Tamara J. Zelikova; Dan R. LeCain; David G. Williams; Jack A. Morgan; Elise Pendall (Global Change Biology, 2015)
Terrestrial plant and soil respiration, or ecosystem respiration (R eco ), represents a major CO 2 flux in the global carbon cycle. However, there is disagreement in how R eco will respond to future global changes, such as elevated atmosphere CO 2 and warming. To address this, we synthesized six years (2007–2012) of R eco data from the Prairie Heating And CO 2 Enrichment ( PHACE ) experiment. We applied a semi‐mechanistic temperature–response model to simultaneously evaluate the response of R eco to three treatment factors (elevated CO 2 , warming, and soil water manipulation) and their interactions with antecedent soil conditions [e.g., past soil water content ( SWC ) and temperature (SoilT)] and aboveground factors (e.g., vapor pressure deficit, photosynthetically active radiation, vegetation greenness). The model fits the observed R eco well ( R 2 = 0.77). We applied the model to estimate annual (March–October) R eco , which was stimulated under elevated CO 2 in most years, likely due to the indirect effect of elevated CO 2 on SWC . When aggregated from 2007 to 2012, total six‐year R eco was stimulated by elevated CO 2 singly (24%) or in combination with warming (28%). Warming had little effect on annual R eco under ambient CO 2 , but stimulated it under elevated CO 2 (32% across all years) when precipitation was high (e.g., 44% in 2009, a ‘wet’ year). Treatment‐level differences in R eco can be partly attributed to the effects of antecedent SoilT and vegetation greenness on the apparent temperature sensitivity of R eco and to the effects of antecedent and current SWC and vegetation activity (greenness modulated by VPD ) on R eco base rates. Thus, this study indicates that the incorporation of both antecedent environmental conditions and aboveground vegetation activity are critical to predicting R eco at multiple timescales (subdaily to annual) and under a future climate of elevated CO 2 and warming.

Disentangling root responses to climate change in a semiarid grassland - Yolima Carrillo; Feike A. Dijkstra; Dan LeCain; Jack A. Morgan; Dana Blumenthal; Sarah Waldron; Elise Pendall (Oecologia, 2014)

Alfalfa-grass biomass, soil organic carbon, and total nitrogen under different management approaches in an irrigated agroecosystem - Rajan Ghimire; Jay B. Norton; Elise Pendall (Plant and Soil, 2014)

Altered root traits due to elevated CO 2 : a meta‐analysis - Ming Nie; Meng Lu; Jennifer Bell; Swastika Raut; Elise Pendall (Global Ecology and Biogeography, 2013)
Aim Plant root traits regulate belowground C inputs, soil nutrient and water uptake, and play critical roles in determining sustainable plant production and consequences for ecosystem C storage. However, the effects of elevated CO 2 on root morphology and function have not been well quantified. We reveal general patterns of root trait responses to elevated CO 2 from field manipulative experiments. Location N orth A merica, E urope, O ceania, A sia. Methods The meta‐analysis approach was used to examine the effects of CO 2 elevation on 17 variables associated with root morphology, biomass size and distribution, C and N concentrations and pools, turnover and fungal colonization from 110 published studies. Results Elevated CO 2 increased root length (+26.0%) and diameter (+8.4%). Elevated CO 2 also stimulated total root (+28.8%), fine root (+27.7%) and coarse root biomass (+25.3%), demonstrating strong responses of root morphology and biomass. Elevated CO 2 increased the root:shoot ratio (+8.5%) and decreased the proportion of roots in the topsoil (–8.4%), suggesting that plants expand rooting systems. In addition, elevated CO 2 decreased N concentration (–7.1%), but did not affect C concentration, and thus increased the C : N ratio (+7.8%). Root C (+29.3%) increased disproportionately relative to root N pools (+9.4%) under elevated CO 2 . Functional traits were also strongly affected by elevated CO 2 , which increased respiration (+58.9%), rhizodeposition (+37.9%) and fungal colonization (+3.3%). Main conclusions These results suggest that elevated CO 2 promoted root morphological development, root system expansion and C input to soils, implying that the sensitive responses of root morphology and function to elevated CO 2 would increase long‐term belowground C sequestration.

Positive climate feedbacks of soil microbial communities in a semi‐arid grassland - Ming Nie; Elise Pendall; Colin Bell; Caley K. Gasch; Swastika Raut; Shanker Tamang; Matthew D. Wallenstein (Ecology Letters, 2013)
Soil microbial communities may be able to rapidly respond to changing environments in ways that change community structure and functioning, which could affect climate–carbon feedbacks. However, detecting microbial feedbacks to elevated CO 2 (eCO 2 ) or warming is hampered by concurrent changes in substrate availability and plant responses. Whether microbial communities can persistently feed back to climate change is still unknown. We overcame this problem by collecting microbial inocula at subfreezing conditions under eCO 2 and warming treatments in a semi‐arid grassland field experiment. The inoculant was incubated in a sterilised soil medium at constant conditions for 30 days. Microbes from eCO 2 exhibited an increased ability to decompose soil organic matter (SOM) compared with those from ambient CO 2 plots, and microbes from warmed plots exhibited increased thermal sensitivity for respiration. Microbes from the combined eCO 2 and warming plots had consistently enhanced microbial decomposition activity and thermal sensitivity. These persistent positive feedbacks of soil microbial communities to eCO 2 and warming may therefore stimulate soil C loss.

Does declining carbon‐use efficiency explain thermal acclimation of soil respiration with warming? - Colin L. Tucker; Jennifer Bell; Elise Pendall; Kiona Ogle (Global Change Biology, 2013)
Enhanced soil respiration in response to global warming may substantially increase atmospheric CO 2 concentrations above the anthropogenic contribution, depending on the mechanisms underlying the temperature sensitivity of soil respiration. Here, we compared short‐term and seasonal responses of soil respiration to a shifting thermal environment and variable substrate availability via laboratory incubations. To analyze the data from incubations, we implemented a novel process‐based model of soil respiration in a hierarchical Bayesian framework. Our process model combined a M ichaelis– M enten‐type equation of substrate availability and microbial biomass with an A rrhenius‐type nonlinear temperature response function. We tested the competing hypotheses that apparent thermal acclimation of soil respiration can be explained by depletion of labile substrates in warmed soils, or that physiological acclimation reduces respiration rates. We demonstrated that short‐term apparent acclimation can be induced by substrate depletion, but that decreasing microbial biomass carbon ( MBC ) is also important, and lower MBC at warmer temperatures is likely due to decreased carbon‐use efficiency ( CUE ). Observed seasonal acclimation of soil respiration was associated with higher CUE and lower basal respiration for summer‐ vs. winter‐collected soils. Whether the observed short‐term decrease in CUE or the seasonal acclimation of CUE with increased temperatures dominates the response to long‐term warming will have important consequences for soil organic carbon storage.

Controls over Soil Nitrogen Pools in a Semiarid Grassland Under Elevated CO2 and Warming - Yolima Carrillo; Feike A. Dijkstra; Elise Pendall; Jack A. Morgan; Dana M. Blumenthal (Ecosystems, 2012)

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Decomposition and nitrogen transformation rates in a temperate grassland vary among co-occurring plant species - Yui Osanai; Anna Flittner; Jasmine K. Janes; Phil Theobald; Elise Pendall; Paul C. D. Newton; Mark J. Hovenden (Plant and Soil, 2012)

Response of soil organic matter pools to elevated CO2 and warming in a semi-arid grassland - Yolima Carrillo; Elise Pendall; Feike A. Dijkstra; Jack A. Morgan; Joanne M. Newcomb (Plant and Soil, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Elevated carbon dioxide alters impacts of precipitation pulses on ecosystem photosynthesis and respiration in a semi-arid grassland - Sarah Bachman; Jana L. Heisler-White; Elise Pendall; David G. Williams; Jack A. Morgan; Joanne Newcomb (Oecologia, 2010)

Wetting and drying cycles drive variations in the stable carbon isotope ratio of respired carbon dioxide in semi-arid grassland - Jee H. Shim; Elise Pendall; Jack A. Morgan; Dennis S. Ojima (Oecologia, 2009)

Response of soil organic matter dynamics to conversion from tropical forest to grassland as determined by long-term incubation - Luitgard Schwendenmann; Elise Pendall (Biology and Fertility of Soils, 2008)

Shrub encroachment in North American grasslands: shifts in growth form dominance rapidly alters control of ecosystem carbon inputs - ALAN K. KNAPP; JOHN M. BRIGGS; SCOTT L. COLLINS; STEVEN R. ARCHER; M. SYNDONIA BRET‐HARTE; BRENT E. EWERS; DEBRA P. PETERS; DONALD R. YOUNG; GAIUS R. SHAVER; ELISE PENDALL; MEAGAN B. CLEARY (Global Change Biology, 2008)
Shrub encroachment into grass‐dominated biomes is occurring globally due to a variety of anthropogenic activities, but the consequences for carbon (C) inputs, storage and cycling remain unclear. We studied eight North American graminoid‐dominated ecosystems invaded by shrubs, from arctic tundra to Atlantic coastal dunes, to quantify patterns and controls of C inputs via aboveground net primary production (ANPP). Across a fourfold range in mean annual precipitation (MAP), a key regulator of ecosystem C input at the continental scale, shrub invasion decreased ANPP in xeric sites, but dramatically increased ANPP (>1000 g m −2 ) at high MAP, where shrub patches maintained extraordinarily high leaf area. Concurrently, the relationship between MAP and ANPP shifted from being nonlinear in grasslands to linear in shrublands. Thus, relatively abrupt (

Effects of forest conversion into grassland on soil aggregate structure and carbon storage in Panama: evidence from soil carbon fractionation and stable isotopes - Luitgard Schwendenmann; Elise Pendall (Plant and Soil, 2006)

Influence of precipitation seasonality on piñon pine cellulose δD values - Elise Pendall (Global Change Biology, 2000)
Summary The influence of seasonal to interannual climate variations on cellulose hydrogen isotopic composition (δD) was assessed by analysing tree rings and needles of piñon pine ( Pinus edulis and P. monophylla ). Sites spanned a gradient of decreasing summer precipitation, from New Mexico to Arizona to Nevada. Tree rings were divided into earlywood, latewood and whole‐year increments, and annual cohorts of needles were collected. The study period (1989–96) included two La Niña events (1989, 1996) and a prolonged El Niño event (1991–95). Winter and spring moisture conditions were strongly related to October–March Southern Oscillation Index (SOI) in New Mexico and Arizona, with above‐average precipitation occurring in El Niño years. Wood δD values at these sites were correlated with winter and spring moisture conditions. Needle δD values were correlated with summer moisture conditions in New Mexico and with winter moisture and SOI in Arizona. Low cellulose δD values observed from 1991 to 1993 in both wood and needles occurred during wet El Niño years, whereas high δD values in needles were present during the dry, La Niña years of 1989 and 1996. North‐eastern Nevada does not receive precipitation anomalies related to ENSO, and thus cellulose δD values did not reflect the ENSO pattern observed at the other sites. Cellulose δD values were strongly, inversely correlated with relative humidity variations at all sites, as predicted by a mechanistic model. Contrary to predictions from the same model and observations from more mesic areas, time series of cellulose δD values were not directly correlated with interannual or seasonal variations in precipitation δD values or temperature at any of the sites. On a regional basis, however, mean δD values in needles and wood were correlated with mean annual temperature and δD values of precipitation. This suggests that temporal averaging may bias relationships between biological systems and climate.